Gale encyclopedia of world history governments. - Gale Group (Detroit, Mich. Gale, 2008)
Provides a broad overview of national governments throughout history, explaining their structures and histories, key players and events, and how governments effect, and are affected by, social change.
Includes bibliographical references and index.
Keywords: World politics -- Encyclopedias; World history -- Encyclopedias; Political science -- Encyclopedias